FILSAFAT KONSTRUKTIVISME: IMPLEMENTASI PEER ASSESSMENT DIGITAL PADA MATA KULIAH MICROTEACHING UNTUK MENINGKATKAN KEMAMPUAN MENGAJAR MAHASISWA CALON GURU - Ni Nyoman Sugihartini; Kustono Djoko (Universitas Pendidikan Ganesha, 2022)
This study aimed to implement peer assessment in microteaching courses as an implementation of constructivism paradigm. Constructivism is a paradigm that supports the student-centered learning process (student center approach). Constructivism believes that the learning process is student-centered, then students are given the opportunity to discover and construct based on their knowledge which can cause students to better remember the material being studied. This research is a research and development (R&D). The R&D model used is the ADDIE model, there are: Analyze, Design, Development, Implementation, Evaluation. The implementation of peer assessment begins with the development of a web-based system, to accommodate student teaching practice videos in microteaching courses, then other students and supporting lecturers provide feedback through the web-based system. The results showed that the student response after implementing the peer assessment was 87.65 which was classified as very positive. However, in this article, it is only focused on the viewpoint of the philosophy of science where the implementation of peer assessment is one of the implementations of the constructivism paradigm, to create prospective teachers in 21st century learning.